Pengaruh Revolusi Industri 4.0 Terhadap Konsumerisme Warga Lokal Desa Sumbersari, Kecamatan Sumbersari, Kabupaten Jember (International Forum of Researchers and Lecturers, 2023)
The technology-based rapid changes that are often referred to as the Industrial Revolution 4.0 have had a major impact on various aspects of people's lives both from Indonesia and the international scene, one of which is the lifestyle of people's consumption. The ease of access to information and the increasing popularity of e-commerce make it easy for people to be tempted to buy things they don't really need. Moreover, it is marked by the presence of social media and digital advertising which reinforces people's lifestyles to become increasingly consumptive with the desired standard of living and forces consumers to buy products that meet these standards. Therefore, it is important for people to understand and be aware of managing their needs within financial limits and use technology wisely to improve their quality of life, thereby avoiding or minimizing a consumptive lifestyle. Researchers will explore this major phenomenon using a descriptive-based qualitative approach. In addition, it is concerned with the theory of Herbert Mead, namely Symbolic Interactionism as a reference for the impact and characteristics that have arisen as a result of the Industrial Revolution 4.0.